Cooperative Self‐Assembly of a Quaternary Complex Formed by Two Cucurbit[7]uril Hosts, Cyclobis(paraquat‐p‐phenylene), and a "Designer" Guest. Issue 38 (17th August 2016) - Tootoonchi, Mohammad Hossein; Sharma, Gaurav; Calles, Jonathan; Prabhakar, Rajeev; Kaifer, Angel E.
Abstract: The self‐assembly in aqueous solution of the well‐known cyclophane, cyclobis(paraquat‐p‐phenylene) (BB 4+ ), and two cucurbit[7]uril (CB7) hosts around a simple hydroquinol‐based, diamine guest (GH2 2+ ) was investigated by 1 H NMR and electronic absorption spectroscopies, electrospray mass spectrometry and DFT computations. The formation of a quaternary supramolecular assembly [GH2 2+ ⋅BB 4+ ⋅ (CB7)2 ] was shown to be a very efficient process, which takes place not only because of the attractive forces between each of the hosts and the guest, but also because of the lateral interactions between the hosts in the final assembly. This complementary set of attractive interactions results in clear cooperative binding effects that help overcome the entropic barriers for multiple component assembly. Abstract : A guest designed and synthesized to have three adjacent binding sites serves as the central component for the highly cooperative assembly of a novel quaternary supramolecular complex. Lateral interactions between the hosts in the final assembly contribute significantly to the cooperative binding.